If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+6x=(5+4)/3-7
We move all terms to the left:
3+6x-((5+4)/3-7)=0
We add all the numbers together, and all the variables
6x+3-(9/3-7)=0
We get rid of parentheses
6x+3+7-9/3=0
We multiply all the terms by the denominator
6x*3-9+3*3+7*3=0
We add all the numbers together, and all the variables
6x*3+21=0
Wy multiply elements
18x+21=0
We move all terms containing x to the left, all other terms to the right
18x=-21
x=-21/18
x=-1+1/6
| 12y-60=780 | | –9+7b=7+9b | | u/3-29=-19 | | 88=c+13 | | 6c+10=10c-6-2c | | x/3+3=-1 | | 15=w-51 | | -3(4x+1)=-39 | | -3(1+6r)=-3r+14+2r | | 4(3x+6)+8x-10=64 | | -8x+-18=10 | | 82=14+4g | | -9d=-8-8d | | 28.12-0.14=p | | (2x+28)=(6x+24) | | 7t+–5t=–4 | | -3y-8=12-y | | -22+3d=-67 | | 25=5x+14 | | –4w=–w−9 | | 12−0.5h=18−2h | | 4x+8=4x+8=4x+8 | | 750-4.9x^2=0 | | 82=2x-8 | | 3(n+3)=–6 | | -10+5m=10+7m | | .x+12=36 | | 7(m+13)=84 | | 750=4.9x^2 | | -.6x+x=20 | | 12+-7+x=2x+-1 | | 3(x–12)=36 |